Primary Giant Cell Tumor of the Breast With Pulmonary Metastasis: A Case Report and Review of the Literature - Zhang, Wenxiang; Kong, Xiangyi; Qi, Yihang; Wang, Xiangyu; Liu, Qiang; Fang, Yi; Song, Yan; Wang, Jing (Frontiers in Oncology, 2021)
Giant cell tumor of soft tissue (GCT-ST) is an extremely rare tumor that is similar in morphology and immunohistochemistry to giant cell tumor of bone, almost 80% of these tumors occur in upper and lower extremities and the breast is a very rare location. Here we report a case of a 65-year-old female patient with a small, mobile palpable lump in the left breast. Although the left breast tumor was considered malignant in preoperative imaging, no evidence of malignant tumor was found by ultrasound-guided core needle biopsy (CNB). Subsequently, the left breast tumor was confirmed as a malignant tumor by intraoperative rapid pathological examination, the initial treatment of the tumor was wide local excision and sentinel lymph node biopsy and it was confirmed to be giant cell tumor of soft tissue by histopathology and immunohistochemistry. Despite surgical treatment achieving clear surgical margins, the patient experienced lung metastases within a year of her initial treatment. Fortunately, the patient underwent surgical treatment of lung metastases, and at the last follow-up, the patient was still alive. This is the first case of a primary soft tissue tumor of the breast that has undergone surgical intervention after lung metastasis. This case report highlights the complexity of clinical diagnosis and treatment of giant cell tumors of soft tissue arising breast. Surgery may be another good treatment when the patient develops lung metastases.